INCREASING COMPETITIVENESS THROUGH OPTIMIZATION OF PRODUCTION COSTS IN THE TEXTILE INDUSTRY (Marketing Journal, 2026)
The article analyzed factors for enhancing the competitiveness of the textile industry through the optimization of production costs. The study examined the structure of production costs, including expenditures on raw materials, energy, labor, № 1 -SON YANVA R, 202 6-YIL 499 and technology, as well as their impact on economic efficiency. A comparative analysis identified the competitive advantages and limiting factors of Uzbekistanʼs textile industry in relation to international producers. The role of lean manufacturing, Indus try 4.0 technologies, and sustainable production principles in reducing costs and improving resource efficiency was substantiated. The findings confirmed that scientifically grounded cost management contributes to strengthening competitive positions and en suring the long -term sustainable development of textile enterprises.
Keywords: textile industry; production costs; competitiveness; cost optimization; lean manufacturing; Industry 4.0; sustainable development